Program Pagelaran Wayang Orang di Radio Republik Indonesia Surakarta Tahun 2011-2021 - Puput Nur Utami (Fakulas Keguruan dan Ilmu Pendidikan, 2024)
This study examines the existence of the Wayang Orang Performance Program at Radio Republik Indonesia Surakarta from 2011 to 2021. The background of this research is the need to preserve traditional Javanese performing arts amid modernization, digital media development, changing public interests, and the COVID 19 pandemic. This research uses historical methods consisting of heuristics, source criticism, interpretation, and historiography. Data were obtained through interviews, observation, documentation, and literature review. The analysis uses a socio-cultural history approach and Talcott Parsons' structural functionalism theory. The results show that the program developed from conventional radio broadcasting into digital media adaptation. In 2011, RRI Surakarta strengthened cultural broadcasting through Wayang Orang Seribu Bintang and the Special Cultural Broadcast Program. In 2019 2020, digital media, audiovisual documentation, YouTube, social media, and online broadcasting expanded its reach. The study concludes that the program's existence was shaped by cultural commitment, institutional adaptation, and collaboration with artists and society. Keywords: existence, Wayang Orang, RRI Surakarta, cultural preservation, socio cultural history.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: Wayang Orang; RRI Surakarta